The Accuracy of Detection and Diagnosis of Oral Lesions by Clinical Dental Students - Tirtania, Carinna; Priandini, Dewi; Nadiah, Najla; Gunardi, Indrayadi; Sathyamoorthy, Hrishikesh (UI Scholars Hub, 2024)
Objective: To determine the accuracy of diagnosing oral lesions through clinical photos taken by clinical dental students (CDS). Methods: The observational analytic study was conducted on 100 CDS to evaluate 140 clinical photos of oral lesions. The gold standard was evaluated by three oral medicine specialists. Data analysis will be performed using accuracy and kappa tests. Results: The accuracy rate of lesion detection in CDS is high (88.55%) with substantial agreement (κ = 0.66). However, the accuracy rate of diagnosis is low (38.21%) with no agreement (κ = -0.30). Participation in the clinical Oral Medicine module positively influenced detection accuracy, with the highest rate among students who had completed the module (96.18%). However, diagnostic accuracy remained low across all groups. Conclusion: CDS demonstrates good detection abilities but struggles with accurate diagnosis. Participation in the clinical Oral Medicine module is beneficial for improving detection abilities. Further efforts are needed to enhance diagnostic skills and ensure that CDS are well-prepared for clinical practice.